Strengthening Teachers’ Professional Competence through Strategic Leadership of Madrasah Principals to Improve the Quality of Madrasah Aliyah Education - Bahruddin, Nurul; Zamroni, Afif; Kausar, Shakila (Journal of Education and Learning Innovation, 2026)
This study aims to examine and discuss in depth the strategies for developing teachers’ professional competence at MA Ma’arif, focusing on three main aspects: (1) the leadership strategies implemented by the school principal, (2) the obstacles encountered in developing teachers’ professional competence, and (3) the recommended model for future professional competence development. This research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The findings indicate that: (1) the principal’s leadership strategy in developing teachers’ professional competence to improve educational quality is carried out through two approaches. The first is a formal strategy in which teachers are assigned by the institution to participate in education and training programs. The second is a non-formal strategy in which teachers independently take the initiative to develop and improve their professional skills related to their duties and positions. (2) Several obstacles in developing teachers’ professional competence include limited mastery of information technology within the school, time constraints, limited teacher creativity in classroom learning processes, insufficient collections of books or school facilities, and the lack of scientific publications produced by teachers. (3) The model that can be used to enhance teachers’ professionalism in carrying out their duties is through an *in-service training* program.